Clinical characteristics in patients with SARS‐CoV‐2/HBV co‐infection. Issue 12 (16th August 2020) - Chen, Liping; Huang, Shaoping; Yang, Jingmao; Cheng, Xin; Shang, Zhiyin; Lu, Hongzhou; Cheng, Jilin
Abstract: COVID‐19 has become a global pandemic and garnered international attention. Although the clinical features of COVID‐19‐related liver injury have been investigated, there have been no reports and studies on the clinical characteristics of COVID‐19 patients co‐infected with hepatitis B virus (HBV). This study aimed to evaluate whether SARS‐CoV‐2/HBV co‐infection could influence liver function and the disease outcome. All 326 confirmed COVID‐19 cases in Shanghai Public Health Clinical Center (The COVID‐19 designated hospital in Shanghai, China) from 20 January 2020 to 24 February 2020 were enrolled and followed up until February 29 in this study. The clinical, laboratory data and the length of stay were collected and analysed retrospectively. 20 patients with HBV co‐infection (6.1%) and 306 patients (93.9%) without HBV infection showed no differences in the level of liver function parameters. However, compared with HBsAg‐ patients [145.4 mg/L (103.9‐179.2)], HBsAg + patients had a lower level of prealbumin [(102.3 mg/L (76.22‐160.2), P = .0367]. There were also no significant differences for the discharge rate and the length of stay between two groups. Taken together, we found no evidence that SARS‐CoV‐2/HBV co‐infection could aggravate liver injury or extend duration of hospitalization.